Effects of Self-Justification on and Nurses’ Commitment to Reducing the Risk of Disease Transmission in Hospitals - Suarnianti; Martiana, Tri; Damayanti, Nyoman Anita (Pakistan Journal of Nutrition, 2016)
The inconsistencies in nurses’ behaviors when they are applying standard precautions is a problem that has great potential to expose them to infectious diseases. Accordingly, nurses must be determined to consistently implement standard precautions; however, nurses tend to believe that their previous actions provide an advantage because of reasons associated with self-justification. This study aimed to investigate the effects of self-justification and the commitment of nurses to reducing the risk of disease transmission in hospitals. This observational analysis applied a stratified random sampling technique that was used to enroll 123 participants. The data were analyzed by simple linear regression. The results showed that 72.1% of the nurses used external strategies of self-justification and had a weak commitment, while 52.7% of the nurses used a strategy of internal self-justification and showed a strong commitment. The simple linear regression results indicated that self-justification significantly influenced nurses’ commitments to display contagion risk reduction behaviors (p = 0.000). This finding implies that nurses should enhance their internal self-justification strategies when experiencing gaps in commitment or when performing unsafe behaviors, which could strengthen their commitment to change high-risk behaviors.